DOP020 Thiopurine monotherapy still has a place in the treatment of patients with mild-to-moderate Crohn's disease in the biological era. (16th January 2018) - Verstockt, B; Boets, L; Van Assche, G; Vermeire, S; Ferrante, M
Abstract: Background: For more than half a century, thiopurines have been the first-line maintenance therapy in patients with Crohn's disease (CD). With the increasing availability of biological drugs, thiopurines are often considered less potent, though in mild-to-moderate disease they may be a valid, safe and less expensive alternative. Genetic determinants including HLA, TPMT and NUDT15 have been associated with response and/or side effects to thiopurines. We here report outcome of thiopurine monotherapy in CD patients, and evaluated genetic associations with response. Methods: The medical records of all genotyped CD patients (Illumina Immunochip) who ever received thiopurine monotherapy at our tertial referral centre were retrospectively assessed. All patients had TPMT-screening prior to thiopurine initiation. Response was defined as continuation of thiopurines for more than 1 year in monotherapy, with minimal corticosteroid use (max 1 course/year) and no need for other rescue therapy. Allelic association was assessed using PLINK v1.07. Results: Over the past 18 years, 852 CD patients (median disease duration 4.0 years) received thiopurine monotherapy (99.8% azathioprine, 9.8% mercaptopurine), of whom a median (IQR) follow-up of 13.3 (8.3–18.3) years is available. One third of patients (35.5%) responded, whereas 35.5% experienced no response. Thiopurine withdrawal due to side-effects occurred in 29.0% of patients, early after initiation (29.2, 14.6–73 days), including pancreatitis ( n = 62), abnormal liver tests ( n = 18) and GI intolerance ( n = 52). Three lymphomas were diagnosed during follow-up. One quarter of responding patients (26.1%) never discontinued therapy during median follow-up of 7.9 (3.1–11.9) years. The other 73.9% initial responders stopped thiopurine therapy after 5.5 (2.8–9.2) years. Ileal disease location ( p = 0.001), older age ( p = 0.04), longer disease duration ( p < 0.001), absence of perianal disease behaviour ( p = 0.004) and absence of active perianal disease at time of thiopurine initiation ( p < 0.0001) were significantly associated with response. Genetic analysis revealed three loci significantly associated with response to thiopurines, including rs10196508 located at a regulatory region within chromosome 2 ( p = 2 × 10 −5, OR = 2.6). Conclusions: In this large retrospective series, thiopurine monotherapy could safely maintain clinical response in up to 35.5% of patients after one year, similar to previous prospective data observed during the SONIC-trial. We identified a genetic marker associated with response to thiopurines, which needs validation in an independent cohort before its clinical use can be evaluated.